The unweighed factor during assessment of systemic lupus erythematosus arthritis - Omneya Mohamed-Ayman; Sally S. Hassouna (SpringerOpen, 2024)
Abstract Background Systemic lupus erythematosus (SLE) is a known multisystemic autoimmune disorder. Active disease causes diverse morbidities. Arthritis is one of disease features present in most of patients, so it is important to study risk factors for such a complaint. Obesity appeared in some studies to increase SLE activity, here in this study, and for the first time, the effect of body weight on arthritis associating the disease was assessed. Methods SLE patients were asked about their joint manifestations and were asked to weigh up joint pain severity which was translated into values of patient self-report joint count (PTJT) present in Multidimensional Health Assessment Questionnaire (MDHAQ), which was then compared to joint examination in the form of 28 tender joint count (28 TJC) and 28 swollen joint count (28 SJC). All previous items were correlated to body mass index (BMI). Results BMI has a significant positive correlation with PTJT p = 0.013, and when PTJT of upper limbs and lower limbs were assessed separately, BMI was also positively corelated with p = 0.008 and 0.049, respectively. Conclusions Increased BMI may be a risk factor for arthritis associated with SLE, regardless its effect on weight-bearing joints. Management of body weight may help in preventing progression of joint affection in SLE.